Beckett, "Molloy": language of silence - García Mora, Mario (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In his German Letter (1937), Beckett wrote about the meaningless of English, his mother tongue: “my own language seems to me more and more like a veil that has to be torn”. To break that veil the autor exposes what will be his literary program point by point. I pretend to use him to understand in depth his first novel: Molloy (1951). At the same time, I would say that the journey cannot be done in one direction: the reading of Molloy from German Letter is parallel to the reading of German Letter from Molloy.
Keywords: Molloy; Beckett; German Letter; language; meaning